195 RANDOMISED TRIAL OF LAPAROSCOPIC NISSEN VS. ANTERIOR 180 DEGREE PARTIAL FUNDOPLICATION—LATE CLINICAL OUTCOMES AT 15–20 YEARS. (14th September 2020) - Rudolph-Stringer, V; Bright, T; Devitt, P; Game, P; Jamieson, G; Watson, D
Abstract:  : Laparoscopic Nissen fundoplication for gastro-oesophageal reflux is followed by troublesome side effects in some patients. Partial fundoplications are proposed for reflux control with less side effects. We reported earlier outcomes from a randomised control trial of Nissen vs. anterior 180° partial fundoplication, with a good outcome following anterior 180° partial fundoplication at up to 10 years follow-up. For this study we determined very late clinical outcomes at up to 20 years follow-up. Methods: 107 patients were randomised to Nissen vs. anterior 180° partial fundoplication. 15–20 year follow-up data was available for 79 (41 Nissen, 38 anterior). Outcome was assessed using a standardised clinical questionnaire that included 0–10 analogue scores and yes/no questions to evaluate reflux symptoms, side-effects and overall satisfaction with surgery. Results: Heartburn (mean score 3.2 vs 1.4, p = 0.001) and proton pump inhibitor use (41.7% vs 17.1%, p = 0.023) were higher, dysphagia for solids (mean score 1.8 vs 3.3, p = 0.015) was less, and ability to belch was better preserved (84.2% vs 65.9%, p = 0.030) after anterior fundoplication. Overall outcome measures were similar for both groups (mean satisfaction score 8.4 vs 8.0, p = 0.444; 86.8% vs 90.2% satisfied with outcome). Six patients underwent revision from anterior to Nissen fundoplication for reflux, and 5 from Nissen to partial fundoplication for dysphagia. Two further patients underwent revision following Nissen fundoplication for reflux and paraoesophageal hernia respectively. Conclusion: At up to 20 years follow-up Nissen and anterior 180-degree partial fundoplication achieve similar rates over overall success, but with a demonstrable trade-off between better reflux symptom control vs. more side-effects after Nissen fundoplication.